Rancangan Standar Prosedur Operasional Perawatan Ulkus Pedis Diabetikum Grade 3 dan 4 - Sri Atun; Blacius Dedi; Ria Sitorus; Asep Badrujamaludin; Hotma Rumahorbo (Jurnal Keperawatan Silampari, 2022)
This study aims to explore nurses' experience treating ulcers in grades 3 and 4 and make it a standard SOP. This research method is qualitative research with an action research approach. The results of the study resulted in five themes, namely the comprehensive treatment of grade 3 and 4 diabetic ulcers, X-ray examination of grade 3 and 4 diabetic ulcers, the role of infrared and ozone in the management of grade 3 and 4 diabetic ulcers, the culture of grade 3 and grade 3 diabetic ulcers. 4, and health education on the five pillars of diabetes mellitus, grade 3, and grade diabetic ulcers. In conclusion, the Operational Service Standards for grades 3 and 4 are expected to be able to make a comprehensive, scientific, and scientific ulcer treatment so that the quality of service is uniform and suitable, the healing process wound quickly, thus avoiding amputation. Keywords: Diabetes Mellitus, Pedis Ulcer Grade 3 and 4